Transport properties of concrete using different repair materials - Azzmi, Norazura Mizal; Ahzahar, Nadira; Hashim, Siti Zubaidah; Zakaria, Intan Bayani; Jamaludin, Nazhatulzakis (Universiti Teknologi MARA, Perak, 2025)
Concrete structures are susceptible to degradation due to external forces and environmental factors, leading to the formation of cracking and spalling. Moreover, the deterioration of concrete, particularly the cover that protects the reinforcing bars, can be attributed to inadequate raw material selection, poor mixture design, and an irregular construction process. These faults reduce the longevity of the structure and result in the structure becoming unserviceable during operation. To successfully address these concerns, it is imperative to promptly undertake concrete repairs to reinstate the safety and functionality of the structures, hence prolonging their operational lifespan. This study aims to ascertain the mechanical characteristics of normal concrete for repair purposes and examine the transport qualities of concrete when applying various repair materials. The inquiry methodology consisted of two distinct phases. The first phase focused on analysing the physical and mechanical properties of concrete. The second phase consisted of investigating the mechanical properties of concrete after being exposed to environmental conditions for 60 days. Three distinct categories of repair materials were chosen, including epoxy, paint, and mortar It has been found that the performance of concrete varies depending on the exposure environment, such as water penetration, carbonation, and chloride immersion, while using different repair materials.